Dengue - Wilder-Smith, Annelies; Horstick, Olaf (The lancet, 2019)
Summary.Mortality from severe dengue is low, but the economic and resource burden on health services remains substantial in endemic settings. Unfortunately, progress towards development of effective therapeutics has been slow, despite notable advances in the understanding of disease pathogenesis and considerable investment in antiviral drug discovery. For decades antibody-dependent enhancement has been the prevalent model to explain dengue pathogenesis, but it was only recently demonstrated in vivo and in clinical studies. At present, the current mainstay of management for most symptomatic dengue patients remains careful observation and prompt but judicious use of intravenous hydration therapy for those with substantial vascular leakage. Various new promising technologies for diagnosis of dengue are currently in the pipeline. New sample-in, answer-out nucleic acid amplification technologies for point-of-care use are being developed to improve performance over current technologies, with the potential to test for multiple pathogens using a single specimen. The search for biomarkers that reliably predict development of severe dengue among symptomatic individuals is also a major focus of current research efforts. The first dengue vaccine was licensed in 2015 but its performance depends on serostatus. There is an urgent need to identify correlates of both vaccine protection and disease enhancement. A crucial assessment of vector control tools should guide a research agenda for determining the most effective interventions, and how to best combine state-of-the-art vector control with vaccination.